Angelina trueheart and the fox - Card, Margaret (Thomas Nelson Melbourne, 1994)
Angelina Trueheart and the Fox is an enchanting children$1 (Bs story that follows the adventures of a brave girl named Angelina and her encounter with a clever fox. As they navigate a magical forest, they form an unexpected friendship and embark on a journey filled with challenges and discoveries. Through their adventures, Angelina learns valuable lessons about courage, trust, and the importance of believing in oneself. Richly illustrated and filled with whimsical elements, this tale captivates young readers and encourages them to embrace their imagination while exploring themes of friendship and resilience.s